Цитогенетические нарушения в озимой пшенице при действии радионуклидных загрязнений зоны отчуждения ЧАЭС через 25 лет после аварии - Якимчук, Р.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. To make a cytogenetic analysis of meristematic cells of primary roots of winter wheat rootlets and to identify the frequency and specter of chromosome disorders induced by radio nuclide contamination of the alienation zone 25 years after the accident at ChNPP. Methods. To make crushed preparations of primary winter wheat roots and their cytogenetic analysis. Results. The frequency of variable cells depending on the winter wheat variety and the soil contamination density is 2.0–7.6 times higher than a spontaneous level. A maximum quantity of cytogenetic disorders was identified when seeds were kept in moist soil with the highest total densities of radio nuclide contamination. The specter of chromosome disorders, found during a cytogenetic analysis as a result of the effect of radio nuclide contamination of all the areas studied, includes the most typical paired fragments and dicentric bridges when ionizing radiation occurs. Conclusions. As there is no correlation between the frequency of variable cells and soil radio nuclide contamination, it questions the possibility of using the indicators of specific radio activity and exposure doze power, in the conditions of radio nuclide contamination, to predict genetic disorders of organisms.

Key words: radio nuclide contamination, T. aestivum L., the ChNPP alienation zone.